A Broader View of Conservation: Mapping Nature and Culture of Working Lands in the Texas Hill Country - Joanna Weathersby; Jason P. Julian (Land)
Working lands are (agri)cultural landscapes with natural value that provide tangible and intangible benefits to people. The development and loss of working landscapes and other rural lands have been increasing, especially in regions experiencing rapid urban growth. To address these issues and conservation needs, we conducted a multi-scale study that involved (1) an in-depth case study of a working ranch focused on conservation, and (2) a geospatial inventory of ecosystem services and cultural values across a Central Texas county that is still dominated by working landscapes yet is experiencing increasing urbanization. The purpose of these two complementary scales was to add a broader view of working landscape values by mapping the multiple benefits they provide and assessing where provisioning, regulating, and cultural benefits overlap. The ultimate objective of our study was to identify target zones for conservation planning. Based on categorical and spatial variation in the mapped benefits inventory, we identified four conservation target zones: Headwaters, Historic Towns, Geologic Significance, and Tourism Corridor. Finally, we framed these conservation target zones within the context of land use decisions and tradeoff analyses.